2010
DOI: 10.1097/sla.0b013e3181ba845c
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Touch Imprint and Frozen Section Analysis of Sentinel Lymph Nodes After Neoadjuvant Chemotherapy for Breast Cancer

Abstract: Intraoperative evaluation of sentinel nodes with touch imprint and frozen section analysis in patients treated with neoadjuvant chemotherapy showed acceptable sensitivity, specificity, and accuracy. Nearly all of the misses in intraoperative evaluation were in patients with micrometastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 15 publications
2
17
1
Order By: Relevance
“…[29][30][31] Although there was a concern that NAC-induced histological changes of metastases and lymph nodes such as fi brosis, fat necrosis, histiocytic accumulation, and granulation tissue formation may interfere with the detection of metastases, our results were comparable with those obtained in early untreated breast cancer. We compared the results of intraoperative frozen-section (FS) analysis in patients treated with NAC and those not treated with NAC.…”
Section: Intraoperative Assessment Of Sentinel Lymph Nodes After Neoasupporting
confidence: 83%
“…[29][30][31] Although there was a concern that NAC-induced histological changes of metastases and lymph nodes such as fi brosis, fat necrosis, histiocytic accumulation, and granulation tissue formation may interfere with the detection of metastases, our results were comparable with those obtained in early untreated breast cancer. We compared the results of intraoperative frozen-section (FS) analysis in patients treated with NAC and those not treated with NAC.…”
Section: Intraoperative Assessment Of Sentinel Lymph Nodes After Neoasupporting
confidence: 83%
“…These figures compare favourably with those for the cases examined with Genesearch in this study (retrospective samples) and in published data . This contrasts with established methods used in the intraoperative setting: FS and DAB cytology . A meta‐analysis of the published literature has indicated that FS analysis has a sensitivity of 76% and that imprint cytology has a sensitivity of 62%, with marked divergence in the range of sensitivities and specificities reported.…”
Section: Discussioncontrasting
confidence: 47%
“…These methodologies have limitations in the context of one‐step axillary clearance. Conventional histopathology has the disadvantage of a delayed time course of 2–3 days, and FS and DABc, although highly specific, have inherent sensitivity issues . The molecular approach has the disadvantages of cost and disruption resulting from the implementation of a new technology, but it offers the advantages of enhanced sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sentinel node procedure at our institution has been described previously [23]. In brief, the sentinel node procedure was performed using the combination technique of blue dye and radioactive isotope.…”
Section: Surgical Outcomesmentioning
confidence: 99%